International non-Governmental Organizations at the Global Governance System: ICAN and the Treaty on the Prohibition of Nuclear Weapons - Rocha, Pedro Diniz [UNESP] (Univ Rosario, Centro Estudios Politicos & Int, 2020)
This article demonstrates how an international non-governmental organization may influence results in an international organization through the initial framing of an issue. Specifically, it aims to understand the role of ICAN (International Campaign to Abolish Nuclear Weapons) in the approval of the Treaty on the Prohibition of Nuclear Weapons (TPNW) by the United Nations General Assembly on July 17, 2017. Methodologically, it is based on process-tracing, with causal mechanisms being constructed based on the theoretical framework proposed by Jutta Joachim (2007). The article is expected to contribute to the literature by proposing to focus on the negotiating process within the international governance system, specifically concerning the role of ingos and their interrelation with other relevant actors in the global arena.
Keywords: Global Governance; nuclear weapons; international non-governmental organization; International Campaign to Abolish Nuclear Weapons; Treaty on the Prohibition of Nuclear Weapons; arms control